COVID-19 Exposure and Family Impact Scales for Adolescents and Young Adults. (23rd April 2022) - Schwartz, Lisa A; Lewis, Amanda M; Alderfer, Melissa A; Vega, Gabriela; Barakat, Lamia P; King-Dowling, Sara; Psihogios, Alexandra M; Canter, Kimberly S; Crosby, Lori; Arasteh, Kamyar; Enlow, Paul; Hildenbrand, Aimee K; et al.
Abstract: Objective: To understand the impact of the coronavirus disease 2019 (COVID-19) pandemic on adolescents and young adults (AYAs), we adapted the COVID-19 Exposure and Family Impact Scales (CEFIS; Kazak et al., 2021 ) for AYAs. Here, we report on the development, structure, and psychometric properties of the CEFIS-AYA. Methods: The CEFIS-AYA was developed by a multidisciplinary, multi-institutional team using a rapid iterative process. Data from 3, 912 AYAs from 21 programs at 16 institutions across the United States were collected from May 2020 to April 2021. We examined the underlying structure of the CEFIS-AYA using principal component analysis (PCA), calculated internal consistencies, and explored differences in scores by gender and age. Results: Participants reported exposure to a range of COVID-19-related events ( M  = 9.08 events, of 28). On the bidirectional 4-point Impact scale, mean item scores were mostly above the midpoint, indicating a slightly negative impact. Kuder–Richardson 20/Cronbach's Alpha was good for Exposure ( α  = .76) and excellent for Impact ( α  = .93). PCA identified seven factors for Exposure (Severe COVID-19, Loss of Income, Limited Access to Essentials, COVID-19 Exposure, Disruptions to Activities, Disruptions to Living Conditions, and Designation as an Essential Worker) and five for Impact (Self and Family Relationships, Physical Well-Being, Emotional Well-Being, Social Well-Being, and Distress). Gender and age differences in CEFIS-AYA scores were identified. Discussion: Initial reliability data are strong and support use of the CEFIS-AYA for measuring the effect of the COVID-19 pandemic on AYAs in research and clinical care.